To scan or not to scan? The economics of transthoracic ultrasonography for ‘whole-flock’ ovine pulmonary adenocarcinoma screening in UK sheep flocks - Davies, P.; Strugnell, B.; Thomas, Lian F.; Lovatt, F.; Willison, I. (Wiley, 2022)
Background Transthoracic ultrasonography (TTUS) is currently the only widely used method to diagnose suspected preclinical or subclinical cases of ovine pulmonary adenocarcinoma/Jaagsiekte (OPA) in live sheep. However, the economic impact of using TTUS as a screening test has not been described previously.